Microalgae a Superior Source of Folates: Quantification of Folates in Halophile Microalgae by Stable Isotope Dilution Assay - Woortman, Dirk Volker; Fuchs, Tobias; Striegel, Lisa; Fuchs, Monika; Weber, Nadine; Brück, Thomas B.; Rychlik, Michael (Frontiers in Bioengineering and Biotechnology, 2020)
A multitude of human nutritional supplements based on Chlorella vulgaris biomass has recently been introduced to the specialty food market. In this study, an analysis of total folate contents in Chlorella sp. and a series of marine microalgae was conducted to evaluate folate content in alternative algae-based food production strains. For the first time, total folate content and vitamer distribution in microalgae were analyzed by stable isotope dilution assay (SIDA) using LC-MS/MS, which has demonstrated its superiority with respect to folate quantification. Consistently, high folate contents were detected in all examined microalgae samples. High folate concentrations of 3460 ± 134 µg/100 g dry biomass were detected in freshly cultivated Chlorella vulgaris, notably also in other well researched microalgae strains. To that end, the highest folate content currently documented for any algae sample was measured in the marine microalgae Picochlorum sp. isolate with values of 6470 ± 167 µg/100 g dry biomass. This calls for alternative products based on other algae biomass. Our data indicate that freshwater and marine microalgae provide extremely high concentrations of folates, which warrant further studies on the regulation of pteroylpolyglutamates in algae as well as on bioaccessibility, absorption, and retention in humans.